Childhood occipital epilepsy of Gastaut: A long-term prospective study - Gönen, Murat; Aytaç, Emrah; Müngen, Bülent (A. CARBONE Editore, 2017)
Aim: Childhood occipital epilepsy of Gastaut is a pure occipital epileptic syndrome that is usually accepted to have benign course. Information about the disease is mostly based on retrospective studies and its prognosis is not clearly defined. We investigated the electro-clinical course and prognostic features of the disease in this prospective study in which clinical follow-up and treatment were standardized as much as possible. Materials and methods: In the study, patients (10 females, 9 males) were followed-up for an average of 9.47 ± 5.47 years (range: 2-17). The seizures were ceased in 16 (84.2%) patients, and remission was achieved in 12 (63.2%). The seizures continued in 3 patients (15.8%) despite mono- or poly-therapy. When we compared the cases with (12 patients) or without remission (7 patients), the age at disease onset was lower in cases without remission (7 ± 5.44 years) compared to those with remission (12.08 ± 2.71 years), (p=0.014). Likewise, the total number of seizures experienced before remission was higher in cases without remission (27 ± 41.04) (median: 12 range: 10-120) compared to those with (6.25 ± 7.84) (median: 4 range: 2-30) (p=0.003). Results: In patients with abnormal EEG at baseline, EEG recordings were normalized in those with remission (100%) but remained to be abnormal in those couldn't achieve remission. Of 5 cases with normal EEG recording from onset to end of follow-up period, remission was achieved in 4 cases but not in one case. Conclusion: Our result indicated that consistently normal EEG recordings or abnormal EEG recordings that normalized during follow-up strongly suggest good prognosis. In addition, we concluded that smaller number of seizures experienced before remission and a relative older age, given the age of onset of the disease, can be indicators of good prognosis.
Keywords: Gastaut; Occipital epilepsy; Prospective study